2012
DOI: 10.4013/nbc.2011.63.06
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre uso do solo e composição de insetos aquáticos de quatro bacias hidrográficas do Estado de São Paulo

Abstract: ResumoAs comunidades de insetos aquáticos de quatro bacias hidrográficas sob diferentes graus de ocupação humana foram analisadas em relação aos usos do solo, à declividade do terreno e às variáveis físicas e químicas da água. As bacias hidrográficas estudadas foram Alto Paranapanema, Peixe, Aguapeí e São José dos Dourados. Amostras de insetos aquáticos foram coletadas utilizando-se cestos com substrato artificial, entre agosto e outubro de 2002. Foram colocadas 18 repetições em cada rio, e os insetos amostrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Fish species with nektonic and benthic habits require external resources (Teresa and Carvalho, 2008), as evidenced by the presence of adult terrestrial insects as well as riparian plant fragments found in stomach contents in this study. Therefore, a well-structured riparian forest is capable of protecting the water environment and preserving water quality (Sonoda et al, 2011;Lobón-Cerviá et al, 2016), including providing allocthonous organic matter which serves as food as well as shelter and habitat for aquatic species (Casatti et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fish species with nektonic and benthic habits require external resources (Teresa and Carvalho, 2008), as evidenced by the presence of adult terrestrial insects as well as riparian plant fragments found in stomach contents in this study. Therefore, a well-structured riparian forest is capable of protecting the water environment and preserving water quality (Sonoda et al, 2011;Lobón-Cerviá et al, 2016), including providing allocthonous organic matter which serves as food as well as shelter and habitat for aquatic species (Casatti et al, 2009).…”
Section: Discussionmentioning
confidence: 99%